The United Nations organization : (in)securing global peace & security - Mentan, Tatah, 1948- (Langaa RPCIG, 2020)
Saving succeeding generations from the scourge of war was the main motivation for creating the United Nations. Given the ongoing conflicts, wars and terrorist attacks today one is forced to ask: Is there Hope for International Peace and Security? Where have the safeguards gone to? Has the United Nations become powerless in the face of absence of the "safeguards"? In this book, Professor Tatah Mentan examines the transformation in UN peace and security operations, analysing its changing role and structure. Tatah Mentan argues that the enemy of peace and security in the global system is the dictatorship of predatory bailed out monopoly capitalism that tells us that building war ships is more important than building alternate energy infrastructure. The real enemies are therefore the publicly bailed-out monopolies, Big Media, Big Pharma, Big Oil, the Military Industrial Complex, etc. that deny the truth about conflicts and insecurity. As he emphasises, the enemies are those who refuse to think critically, not being intellectually curious, and accepting the supremacist, fascist, and misgovernance that is reducing the world collectively to being cogs in a diabolical machine of neoliberal global capitalism.